Mitochondrial proteins and congenital birth defect risk: a mendelian randomization study - Xin-yu Li; Da-tao Li; Yi-yuan Li; Zhi-cheng Xu; Qun Zhang; Xia Chen; Feng Xu; Ru-hong Zhang (BMC Pregnancy and Childbirth)
Abstract Background Mitochondrial dysfunction has been hypothesized to play a role in the etiology of congenital birth defects. However, evidence from observational studies is susceptible to bias and confounding. Mendelian randomization uses genetic variants as instrumental variables to investigate causal relationships. This study aimed to investigate the causal effect of mitochondrial proteins on risk of common congenital defects including orofacial clefts, congenital heart defects, external ear malformations, urinary system malformations, nervous system malformations, and limb malformations. Methods Summary statistics data on congenital birth defects were obtained from the FinnGen consortium. This included 1,994 cases of congenital heart malformations, 258 cases of nervous system malformations, 185 cases of ear malformations, 813 cases of urinary system malformations, 92 cases of limb malformations, and 181 cases of cleft lip and cleft palate, alongside 216,798 to 218,611 controls, depending on the defect type. Data on genetic variants associated with 66 mitochondrial proteins were extracted from the Human Plasma Proteome Atlas (n = 3,301 healthy individuals). The inverse-variance weighted method was applied as the primary analysis, with sensitivity analyses using MR-Egger regression, weighted median estimation, and MR-PRESSO to assess pleiotropy and outliers. Results Among the 66 mitochondrial protein traits examined, several displayed significant associations with congenital birth defects. Negative associations were found between pyruvate dehydrogenase kinase isozyme 1 and ATP synthase subunit beta mitochondrial levels and congenital heart malformation risk. GrpE protein homolog 1 mitochondrial was negatively associated with cleft lip/palate risk. 39S ribosomal protein L14 and GrpE protein homolog 1 mitochondrial showed positive and negative links with urinary malformations, respectively. Positive associations were noted between cytochrome c oxidase subunit 4 isoform 2, protein SCO1 homolog, and tRNA pseudouridine synthase A mitochondrial and nervous system malformations, while peptide chain release factor 1-like mitochondrial was negatively related. Cytochrome c oxidase subunit 7 A1 mitochondrial associated positively with ear malformations. Positive relationships were identified between cytochrome c oxidase subunit 7 A1, ADP-ribose pyrophosphatase, coiled-coil-helix-coiled-coil-helix domain-containing protein 10, NFU1 iron-sulfur cluster scaffold homolog mitochondrial, and limb malformation risk. Meanwhile, NADH dehydrogenase [ubiquinone] iron-sulfur protein 4 mitochondrial displayed a negative association. Conclusions This Mendelian randomization study provides evidence that mitochondrial protein levels may be causally implicated in congenital heart, urinary, nervous system, ear, and limb malformations. The findings highlight potential etiological roles for mitochondrial dysfunction in the pathogenesis of structural birth defects. Further large-scale and functional investigations are warranted to corroborate these genetic inference results and elucidate underlying mechanisms that may inform translational applications.